Blood Lipid Profile in Acute Coronary Syndrome and Chronic Stable Angina Patients (Bangladesh Journal of Medical Biochemistry, 2015)
This study was designed to compare the blood lipid profile and conventional cardiovascular risk factors in patients with acute coronary syndrome (ACS) and chronic stable angina (CSA). A total of 110 patients, 55 of which were of ACS and 55 with chronic stable angina (CSA) who underwent coronary angiography in the Department of Cardiology, BSMMU, Dhaka were enrolled for the study. Lipid profile and age, sex, diabetes mellitus, hypertension, hyperlipidemia, smoking habit, family history of premature coronary artery diseases (CAD) of the patients were recorded and compared. Mean±SD age of the studied patients was 52.2±10 years. Prevalence of diabetes mellitus (p